Process Exploration and Flavor Analysis of Oyster Enzymatic Hydrolysates by Lactiplantibacillus pentosus Fermentation - Ke LI; Jianzhong ZHANG; Xinxing XU; Li LIU; Guixin HAN; Hongjiang WANG; Yuanhui ZHAO (Shipin gongye ke-ji, 2024)
In order to investigate the effects of fermented oyster enzymatic hydrolysates on the quality of oyster juice, this study firstly identified oyster species suitable for the processing of oyster juice and established an exclusive sensory descriptive library for oyster juice. And then, through single-factor experimental analysis based on sensory scores and amino acid nitrogen content, the optimal fermentation conditions were determined. The free amino acids, volatile flavor components, and sensory properties were compared between unfermented oyster hydrolysates, fermented oyster hydrolysates, and seasoning fermented oyster hydrolysates. The results showed that Rushan oysters (Crassostrea gigas) were selected for oyster juice processing and an exclusive sensory descriptive library was developed. Lactiplantibacillus pentosus was vaccinate as the fermenting agent. Optimum fermentation condition was at 37 ℃ with the inoculum of 7% for 3 h. Under the optimized conditions, both the amino nitrogen content and flavor were significantly improved. The optimal flavoring conditions for the fermented oyster hydrolysates involved high temperature and pressure treatment (100 kPa, 121 ℃, 20 min) with 8% glucose addition and 2% salt addition, followed by volume concentration to 50% of the original. These conditions resulted in further enhancement of amino nitrogen content with the content of 1.06±0.03 g/100 g and aroma. Additionally, fermentation led to a significant increase (P<0.05) in umami and sweet amino acids, while the content of bitter amino acids decreased significantly (P<0.05). Moreover, the fermented and seasoned treatments effectively reduced the presence of undesirable volatile compound s such as hexanal, 1-penten-3-ol, 3-methylbutanal, and (E,E)-2,4-heptadienal in the oyster hydrolysate, while the level of pleasant compounds was increased such as pyrazine (desirable baking odor). In conclusion, Lactiplantibacillus pentosus fermentation proved to be beneficial in improving the quality of oyster hydrolysates, providing novel insights for the enhancement of oyster juice processing techniques.